Improving Basic Color Recognition Skills Through Drawing Activities in Playgroups at Sahabat Galaxy Kindergarten Bekasi - Kasiati, Kasiati; Lily Yuntina; Delina Kasih (Bulletin of Early Childhood, 2025)
This classroom action research was motivated by the low ability of children in the Sahabat Galaksi Bekasi kindergarten playgroup to recognize basic colors, distinguish mixed colors, and understand the results of mixing primary colors. This study aimed to determine the improvement in the ability of 3-4-year-old children to recognize basic colors through drawing activities. The method used was Kemmis and McTaggart's classroom action research model, which was carried out in two cycles. The research subjects consisted of 10 children, namely 3 boys and 7 girls. Data were collected through observation, interviews, and documentation, then analyzed descriptively and quantitatively with an emphasis on comparing the average scores for each cycle. The results showed an increase in children's basic color recognition skills, from 33% in the pre-cycle to 73% in Cycle I and 86% in Cycle II. These findings prove that drawing activities are effective in improving basic color recognition skills in early childhood.